[Paso Robles neighborhood] - Betty Liliana Banderas Martinez::::::::: (2005)
Description supplied by photographer: 'Esta es una foto de niñitas jugando en mi vecindario en Paso Robles. Mucha gente de San Juan Nuevo vive en el mismo vecindario. Tomé esta foto porque me hizo recordar de mi niñez cuando pasaba el tiempo jugando en la calle con mi amiga Rosa Antolino.' Translation of description: 'A couple of young girls playing in my neighborhood in Paso Robles. Many people from San Juan Nuevo live in the same neighborhood. I took this photo because it reminded me of my childhood when I would always be outside playing with my old friend Rosa Antolino.'